Maneuvers : the international politics of militarizing women's lives - Enloe, Cynthia H., 1938- (University of California Press, 2000)
Enloe outlines the dilemmas feminists around the globe face in trying to craft theories and strategies that support militerized women, locally and internationally, without unwittingly being militerized themselves.
Keywords: Women and the military.; Women and war.; Femmes et armée.; Femmes et guerre.; TECHNOLOGY & ENGINEERING -- Military Science.; HISTORY -- Military -- Other.; SOCIAL SCIENCE -- Gender Studies.; Women and the military; Women and war; Kriegsverbrechen; Militär; Frau; Krieg; Oorlogvoering.; Sociale aspecten.; Militarisering.; Electronic book.